Propolis, Colophony, and Fragrance Cross-Reactivity and Allergic Contact Dermatitis. Issue 3 (May 2016) - Shi, Yiwen; Nedorost, Susan; Scheman, Loren; Scheman, Andrew
Abstract : Background: Colophony and propolis are among the complex plant resins used in a wide variety of medicinal and personal care products. A number of studies of colophony, propolis, and fragrance mixes suggest that contact with one of these allergens may increase the risk of delayed-type hypersensitivity reactions with additional compounds of significant cross-reactivity. Objective: The aims of this study were to determine rates of cross-reactivity between propolis, colophony, and different fragrance mixes and to determine significant cross-reactivity thresholds for which to counsel patient avoidance. Methods: Rates of cross-reactivity were calculated from the databases of 2 midwestern US patch testing centers. Rates were calculated both separately and collectively. Conclusions: For patients allergic to colophony, fragrance and propolis may be considered significant cross-reactors. For patients allergic to propolis, fragrance and colophony may be considered significant cross-reactors. Cross-reactions between colophony, propolis, and fragrance mixes are unidirectional so, for patients allergic to fragrance, cross-reaction to propolis or colophony is not significant. Colophony allergy is found in only a small number of fragrance-allergic patients and is not a good indicator for fragrance allergy.